The epistemology of Physical Education in relation to the curriculum in Secondary Organic Law of Education - Antonio Baena Extremera; Antonio Granero Gallegos; Manuel Gómez López (FEADEF, 2009)
All discipline must define what is and what the deals are concerned, for using knowledge known, (the epistemology), being able to move forward and create a specific knowledge that is consistent with and complementary to that generated by other scientific disciplines. The aim of this article is to make an epistemological approach to currículum of Physical Education at the Secondary School, from its origins to the new Education Law.